A limited market: the recruitment of gay men as surrogacy clients by the infertility industry in the USA - Jacobson, Heather (Reprod Biomed Soc Online, 2018)
Gestational surrogacy via egg donation is an expensive – and sometimes ambivalently undertaken – but increasingly popular route to planned fatherhood for some gay men. The surrogacy market in the USA plays an important role for gay men with the financial resources to access these services, as it is currently the only stable, commercial market in which there are legal protections for openly gay men. While a small, ethnographic and qualitative literature on the experiences of gay fathers via surrogacy exists, less is known about the state of the surrogacy industry towards gay men as clients. Here I investigate the surrogacy industry in the USA to ask how welcome gay men are in this market. I do so via a content analysis of patient/client recruitment on infertility clinic and surrogacy agency websites. Content analysis of 547 websites indicates that the majority of infertility clinics (62%) and 42% of surrogacy agencies do not directly advertise or appear to be welcoming to gay men. A minority of gay-friendly clinics and agencies, which cluster geographically, actively recruit gay men, creating a limited but niche market. The unequal recruitment of gay men as infertility clients reflects how normative ideas about gender, sexuality and social class are reproduced in the infertility industry. This, in turn, may impact gay men's procreative consciousness and decision-making about parenting, and exacerbate inequalities around their access to intentional genetic parenthood.